ASSESSMENT OF THE EFFECTIVENESS OF LOANS AND THE INFLUENCE OF THE RELATIONSHIP QUALITY OF THE DEVELOPMENT PARTNER ON THE FINANCIAL PERFORMANCE OF MSES IN THE MSE FINANCING PROGRAM FOR THE TJSL UNIT PT DAHANA (PERSERO) - Asep Kurniawan; Indah Umiyati; Obi Pangestu (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
This study was conducted to determine whether there is an effect of loan effectiveness and relationship quality on the financial performance of MSEs, either partially or simultaneously. The data used in this study is primary data, with the help of a questionnaire or questionnaire in the form of a google form. The data collection method in this study used a non-probability sampling approach with a purposive sampling technique. The number of samples in this study were 70 respondents, who were foster partners of PT Dahana (Persero) in Subang Regency. The data is processed and tested using data quality test methods, classical assumption tests, multiple regression analysis, and hypothesis testing